Effect of Zingiber officinale on spasm - Hisamuddin, Nadia; Kamarudin, Nur Nadhirah; Sulaiman, Mohd Roslan; Shaik Mohamed Mossadeq, Wan Mastura (Universiti Putra Malaysia Press, 2019)
Zingiberaceae is one of the largest plant families consisting of rhizomes that are commonly used as spice in soups and curries as well as alternative medications in folklore medicine. Zingiber officinale or commonly known as ginger is extensively employed in Asian, Ayurvedic, Chinese, and Arabian folklore medicine for the treatment of pain, inflammation and various spasm-associated gastric ailments. The past few decades saw rapid advancements in the extraction process of ginger bioactive constituents and validation of their corresponding pharmacodynamic and pharmacotherapeutic activities, and biological properties in vivo and in vitro. Results reported from several biological studies on ginger showed that extracts and compounds from this tuberous rhizome exhibit antiemetic, anticancer, antipyretic, antispasmogenic and antimicrobial activities. This article reviews the effect of Zingiber officinale and its bioactive constituents on isolated organ preparations from several species of animals in view of its potential use as an alternative treatment for muscle spasms and common gastric ailments.